Regional Potential Information System: Implementing Extreme Programming Methodology for Sustainable Development - Sihombing, Denny Jean Cross (Jurnal Info Sains : Informatika dan Sains, 2024)
This research focuses on developing a Regional Potential Information System by applying the Extreme Programming (XP) method. This system aims to collect, manage, and present information related to the potential and resources owned by a region, involving aspects such as natural, cultural, economic, social, and infrastructure resources. The research stages include comprehensive data collection, application development with the XP Method, and user acceptance analysis. Data collection involved interviews, document analysis, and field surveys to form the basis of system functionality. Application development was conducted iteratively, focusing on improving functionality that is adaptive and responsive to change. User acceptance analysis involved evaluations from local governments, companies, and communities. The results showed success in designing the system structure, adding functionality incrementally, and getting positive feedback from stakeholders. The contribution of this research lies in the in-depth understanding of the application of the XP Method in the development of the Regional Potential Information System, providing direct practical benefits and a policy basis for the local government.